Effect of Inoculations of Trichoderma viride and Saccharomyces cerevisiae Mixed Culture on Chemical Composition, Fiber, Digestibility and Theobromine Cocoa Pod Fermentation - Muhammad Askari Zakariah (Hasanuddin University, 2016)
The objective of the study was to identify the effect of Trichoderma viride andSaccharomyces cerevisiae inoculant on chemical compositions, digestibility, and theobromineconcentration of fermented cocoa pod. This experiment consisted of four treatments,namely cocoa pods without fermentation as control (R0); fermentation of cocoa pods withinoculant T. viride (R1); fermentation of cocoa pods with inoculant S. cerevisiae (R2); andfermentation of cocoa pods with inoculant T. viride and S. cerevisiae mixed culture (R3).Each treatment had 3 replicates, and then was fermented for 10 days. Variables observedwere the chemical compositions i.e dry matter (DM), organic matter (OM), crude protein(CP), ether extract (EE), crude fiber (CF), nitrogen free extract (NFE), fiber fraction (Neutraldetergent fiber and acid detergent fiber), in vitro digestibility, and theobromine concentration.Data were analysed by one-way analysis of variance and followed by Duncan’s new multiplerange test (DMRT), if there were any significant difference. Results showed the inoculumaffected (P<0.05) the chemical composition, fiber fraction and in vitro digestibility. However,theobromine was not detected on cocoa pod without fermentation and fermentation.Compared to group R0, inoculation with T. viride and S. cerevisiae mixed culture (P<0.05)resulted in higher DM concentration (92.78% vs 89.72% respectively), higher CP (7.43% vs5.63% respectively), higher NDF (79.41% vs 61.18% respectively), higher ADF (73.04%vs 47.94% respectively), but was not significantly different on DM and OM digestibility(21.22% vs 22.24%, and 22.67% vs 24.31% respectively) than cocoa pod without fermentation.It is concluded that inoculant T. viride and S. cerevisiae mixed culture increased CPconcentration, but had no effect on in vitro digestibility.